EFEKTIVITAS DESIGN BRIEF SEBAGAI PROMPT BERBASIS TEKS DALAM PROSES DESAIN LOGO ARTIFICIAL INTELLIGENCE - Hendrawan, Angga (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Artificial Intelligence (AI) has been utilized to solve various human problems, including in the field of design. In design practice, collaboration between humans and AI requires a connecting medium in the form of a design brief that functions to convey ideas in a structured manner. This study uses an experimental method to test the effectiveness of using a design brief formulated in the form of a text prompt to produce a logo design through ChatGPT artificial intelligence. The purpose of this study is to what extent a text-based design brief can be operationalized as a prompt by ChatGPT in producing an ideal logo design that meets six aspects: feasibility, originality, timeliness, relevance, functionality, and sustainability. The results of the study show that ChatGPT is able to understand and translate a brief design in Indonesian into a visual representation in the form of a logo. In general, ChatGPT produces designs that meet the aspects of simplicity, relevance, and errors. However, there are limitations in the aspects of originality and timeliness, as seen from the similarity of the design to previously existing logos. These findings indicate that although AI can be used as an exploratory tool in the design process, assistance from human designers is still needed to ensure the uniqueness and visual durability of the resulting design.